AN ANALYSIS OF STUDENTS’ WRITING SKILL ON ENGLISH EXPOSITORY TEXT - Evi Pebri Ila Rachma (Pusat Riset dan Inovasi Nasional, 2022)
This study analyzed the writing skills in English expository text. There are five indicators in writing expository text: content, organization, grammar, vocabulary, and mechanics. This study aimed to investigate the students' writing skill on expository text related to the five indicators of English expositorytext and investigated the difficulties in writing English expository text. This research study used a descriptive quantitative research design. The participants were first semester students at English Literature Study Program of Universitas Trunojoyo Madura. The data collected from students' writing expository text test and analyzed by using Heaton’s theory. The result data analysis showed that: 1) 47% of students were average to good in writing content, 2) 51% of students were average to good in writing organization, 3) 31% of students were average to good in using grammar, 4) 36% of students were very good to excellent in using vocabulary, 5) 44% of students were very good to excellent in writing mechanics. This research found some difficulties the students when writing expository text. First, students cannot develop their ideas. Second, students are unable to develop their idea based on topic that they have to explain in expository text. Third, students struggle with grammatical structure of expository text. That means, they have to more understand about the simple present tense. Fourth, they were difficult to select appropriate vocabulary when writing expository text. The last, they miss-spelt words and were unsure of proper punctuation that was causing an error of mechanics.